KESANTUNAN BERBAHASA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK ISLAM TERPADU KARAKTER ANAK SHALIH KOTA PADANG - Shafira Nabila, Indah; Nenny Mahyuddin; Yaswinda; Rismareni Pransiska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language politeness is an important aspect of character building and the social development of early childhood. This study aimed to determine the level of language politeness among children aged 5-6 years at Taman Kanak-kanak Islam Terpadu Karakter Anak Shalih, Padang City, based on Geoffrey Leech’s theory of language politeness. This study employed a quantitative approach using a descriptive method. The population as well as the sample consisted of 20 children aged 5-6 years selected using the total sampling technique. Data were collected through structured observation using a rating scale observation sheet consisting of 12 statements representing three indicators: the Tact Maxim, the Generosity Maxim, and the Approbation Maxim. The data were analyzed using descriptive statistics, including mean scores and percentages. The results showed that the children's level of language politeness was in the moderate category, with a mean score of 2.99 and a percentage of 74.75%. These findings indicate that the children's language politeness has developed at a moderate level; however, continuous habituation and stimulation are still needed to optimize its development